The Mental Health Education Needed Child Violent Victims with Post Traumatic Stress Disorder in Sumatera Barat - Febri Tri Andini; Yulastri Arif; Feri Fernandes (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Victims of violence such as children who experience psychic trauma when not properly handled can experience Post Traumatic Stress Disorder (PTSD). Post-Traumatic Stress Disorder is a result of disasters or calamities such as accidents, natural disasters, war or violence that cause disruptions such as anxiety and impaired self-integrity. There are several factors that cause a person to experience PTSD, one of which is a factor associated with traumatic events. This research aims to know the education of mental health needed by children of violence with PTSD. The design of this research uses a type of quantitative research that is descriptive. The location of this research is six regencies/cities in West Sumatra province, namely Padang City, Agam Regency, Solok Regency, Solok City, Pariaman Regency and District 50 Kota. The sample samples amounted to 106 students taken using the Multistage Sampling technique. The measuring instrument used is a violent questionnaire, Mini ICD10 Questionnaire, DSM V questionnaire and questionnaire to determine the mental health education that children need with PTSD. Data analysis using the SPSS application and research results in the form of frequency distribution.The results of this study were 34.9% of children's violent victims with PTSD chose positive thinking education as a form of education needed..